2018
DOI: 10.21308/recp.46.05
|View full text |Cite
|
Sign up to set email alerts
|

Mayors facing local government reforms: from muncipal organization leadership to public management transformation processes

Abstract: Local public authorities have traditionally been an area for experimenting with reforms of varying impact for the overall institutional framework. In implementing these reforms, a prominent part has been taken by mayors in their role as the highest-ranking officials in their organisations. This article reports evidence for, and reflects on, the connection between the figure of the Spanish mayor (in the way mayors perceive their own role) and their relations with both the municipal governments they head and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The results of Goo (2015), Ospina & Foldy (2010), and Sanyal and Hisam (2018) showed that the principal is the main actor in the role as a determinant or key in the factor of change and excellence of school resources. Also, the study of Salvador (2018) about leadership that can improve school performance and development revealed that it is important to communicate and sustain vision to build a collaborative learning environment. Molina (2018), and Naile and Selesho (2014) revealed that visionary leadership can increase organizational effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of Goo (2015), Ospina & Foldy (2010), and Sanyal and Hisam (2018) showed that the principal is the main actor in the role as a determinant or key in the factor of change and excellence of school resources. Also, the study of Salvador (2018) about leadership that can improve school performance and development revealed that it is important to communicate and sustain vision to build a collaborative learning environment. Molina (2018), and Naile and Selesho (2014) revealed that visionary leadership can increase organizational effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As head of staff, the typical Spanish mayor is closely involved in running and managing the local government. The mayoral powers of appointment are considerable and they are often used to intervene and act in the organization and operation of municipal organizations (Salvador & Pano, 2018).…”
Section: Spanish Contextmentioning
confidence: 99%
“…Significant attention to the study of the relationship of political processes with public administration in the context of the current stage of civilization, and foreign researchers, including. Kondratenko (2020), Schwab and Mallere (2020), Willmott (2019), Salvador and Pano (2018), Osorio (2018), Phillips (2019), Othman and Yusoff (2020), Cnossen (2019).…”
Section: Introductionmentioning
confidence: 99%